Genetic Modifiers of Cardiorespiratory Fitness Response to Lifestyle Intervention - Peter, Inga (2014)
PURPOSE: Numerous prospective studies indicate that improved cardiorespiratory fitness reduces type 2 diabetes (T2D) risk and delays disease progression. We hypothesized that genetic variants modify fitness response to an intensive lifestyle intervention (ILI) in the Action for Health in Diabetes (Look AHEAD) randomized clinical trial, aimed to detect whether ILI will reduce cardiovascular events in overweight/obese subjects with T2D compared to a standard of care. METHODS: Polymorphisms in established fitness genes and in all loci assayed on the Illumina CARe iSelect chip were examined as predictors of change in metabolic equivalent (MET) level, estimated using a treadmill test, in response to a one-year intervention in 3,899 participants. RESULTS: We identified a significant signal in previously reported fitness-related gene RUNX1 that was associated with one-year METs response in ILI (0.19±0.04 MET less improvement per minor allele copy; P=1.9×10(−5)) and genotype-intervention interaction (P=4.8×10(−3)). In the chip-wide analysis, FKBP7 rs17225700 showed a significant association with ILI response among subjects not receiving beta-blocker medications (0.47±0.09 METs less improvement; P=5.3×10(−7)), and genotype-treatment interaction (P=5.3×10(−5)). GRAIL pathway-based analysis identified connections between associated genes, including those influencing vascular tone, muscle contraction, cardiac energy substrate dynamics, and muscle protein synthesis. CONCLUSIONS: This is the first study to identify genetic variants associated with fitness responses to a randomized lifestyle intervention in overweight/obese diabetic individuals. RUNX1 and FKBP7, involved in erythropoesis and muscle protein synthesis, respectively, are related to change in cardiorespiratory fitness in response to exercise.